Artificial feeding of ixodid ticks - Waladde, S.M.; Young, A.S.; Morzaria, S.P. (Elsevier, 1996)
Ixodid ticks are economically important as they cause direct damage to livestock and are vectors of several pathogens that cause diseases in humans and animals. Some of the important tick-borne pathogens of livestock are Theileria parva, T. annulata, Babesia bigemina, B. bovis, Anaplasma marginale and Cowdria ruminantium. These pathogens are responsible for causing enormous losses in livestock. Identification of factors that influence transmission and development of these pathogens in ticks will greatly facilitate development of rational strategies for control of tick-borne diseases. This research has been hampered by the lack of suitable artificial feeding methods. This paper reviews recent developments in the artificial feeding of ixodid ticks and evaluate how this method can potentially be exploited. It uses as an example the transmission of an important livestock pathogen, T. parva, by Rhipicephalus appendiculatus.